Distribución y abundancia de gasterópodos en las macrófitas de un arroyo de llanura - Pezzani, S. (2006)
The gasteropods distribution was studied and it was analyzed the influence of the aquatic macrophytes biomass fluctuation and the structuring environmental factors. Sampling was carried out in Las Flores stream, a Lujan river tributary, from April 2000 to February 2002. Egeria densa (submerged), Hydrocotyle ranunculoides and Alternanthera philoxeroides (rooted) were the most representative macrophytes. Heleobia piscium and Gundlachia concentrica occurred as the dominant gasteropods. For all other associated macroinvertebrates on macrophytes, Hyalella sp. was predominat. The rainfall and the consequent inflow increase were influenced on the macrophytes biomass and their associated fauna. The macrophytes biomass was one of the factor related to the temporal abundance of gasteropods. However, these variations in the abundance of the gasteropods were more related with the life cycle. Their largest gasteropods and anfipods density was shown on rooted macrophytes. Heleobia piscium, G. concentrica and Hyalella sp. coexist on the same macrophyte during the low abundance periods without any competition. Although, during the breeding period, the displacement of the other macroinvertebrates populations was observed. This suggests interespecific competition by substrate and food between the two gasteropods species while the competition with the anfipods is mainly by substrate. Gasteropods and anfipods consume different type of food. Heleobia piscium and G. concentrica colonize these macrophytes with some preferance. These gasteropods are opportunists species whose distribution and supervivence strategy is as follow: to colonize different aquatic macrophytes showing each species some preference by sumerged or rooted macrophytes; to have an annual breeding period with a high recruitment of individuals which allow to maintain the populations despite the disturbances effect.